Cosmic metal density evolution in neutral gas: insights from observations and cosmological simulations - Yates, Robert M.; Péroux, Céline; Nelson, Dylan (Monthly notices of the Royal Astronomical Society, 2021)
We contrast the latest observations of the cosmic metal density in neutral gas (⁠ρmet,neu⁠) with three cosmological galaxy evolution simulations: L-Galaxies 2020, TNG100, and EAGLE. We find that the fraction of total metals that are in neutral gas is <40 per cent at 3 ≲ z ≲ 5 in these simulations, whereas observations of damped Lyman-α (DLA) systems suggest ≳ 85 per cent. In all three simulations, hot, low-density gas is also a major contributor to the cosmic metal budget, even at high redshift. By considering the evolution in cosmic SFR density (⁠ρsfr⁠), neutral gas density (⁠ρHI⁠), and mean gas-phase metallicity (⁠[⟨M/H⟩]neu⁠), we determine two possible ways in which the absolute ρmet,neu observed in DLAs at high redshift can be matched by simulations: (i) the ρsfr at z ≳ 3 is greater than inferred from current FUV observations, or (ii) current high-redshift DLA metallicity samples have a higher mean host mass than the overall galaxy population. If the first is correct, TNG100 would match the ensemble data best, however there would be an outstanding tension between the currently observed ρsfr and ρmet,neu⁠. If the second is correct, L-Galaxies 2020 would match the ensemble data best, but would require an increase in neutral gas mass inside subhaloes above z ∼ 2.5. If neither is correct, EAGLE would match the ensemble data best, although at the expense of overestimating [⟨M/H⟩]neu⁠. Modulo details related to numerical resolution and H i mass modelling in simulations, these incompatibilities highlight current tensions between key observed cosmic properties at high redshift.
Gesehen am 07.01.2022